A review of FOCUS: Papers in English Literary and Cultural Studies XI. 20th Anniversary Issue - Varga, Zsanett (AMERICANA E-journal of American Studies in Hungary, 2018)
FOCUS: Papers in English Literary and Cultural Studies XI. 20th Anniversary Issue Csaba Maczelka, Andrew C. Rouse, Lívia Szélpál eds. Pécs: Kronosz Kiadó, 2018 151 pages ISSN: 1585-5228